2009
DOI: 10.1007/s10517-010-0823-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum sFas, Leptin, and VEGF in Patients with Ovarian Cancer and Benign Tumors

Abstract: The initial levels of soluble Fas antigen (sFas), leptin, and vascular endothelium growth factor (VEGF) were measured in the sera of 100 patients with ovarian cancer and benign tumors and in 60 healthy women aged 28-65 years. Serum levels of sFas and VEGF were elevated in the total group of patients with ovarian tumors, while leptin levels were the same as in healthy women. The studied parameters did not depend on the age of patients and healthy women. The levels of sFas and leptin were virtually the same in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…These results have been confirmed by a more recent analysis of a larger series and longer followup (Figures 3(a) and 3(b) show the updated results). Finally, in recent studies serum Fas protein (sFas) levels and serum VEGF levels have been found to be increased in ovarian cancer patients correlated with a short duration of the relapse-free period [137]. …”
Section: Cytokines Growth Factors and Association With Lymphocytementioning
confidence: 99%
“…These results have been confirmed by a more recent analysis of a larger series and longer followup (Figures 3(a) and 3(b) show the updated results). Finally, in recent studies serum Fas protein (sFas) levels and serum VEGF levels have been found to be increased in ovarian cancer patients correlated with a short duration of the relapse-free period [137]. …”
Section: Cytokines Growth Factors and Association With Lymphocytementioning
confidence: 99%
“…This shorter product is soluble and inhibits FAS‐mediated cell death, presumably by binding competition for the FAS ligand . High levels of serum soluble FAS have been reported in cancer patients, including ovarian cancer . However, in vitro, in the conditioned medium of primary ovarian cancer cells, the levels of soluble FAS were minimal and not significantly different from those of normal ovarian cells .…”
Section: Discussionmentioning
confidence: 99%
“…62 High levels of serum soluble FAS have been reported in cancer patients, including ovarian cancer. [63][64][65] However, in vitro, in the conditioned medium of primary ovarian cancer cells, the levels of soluble FAS were minimal and not significantly different from those of normal ovarian cells. 57 Similarly, we have demonstrated that soluble FAS protein was undetectable in OVCAR-3 cells.…”
Section: Figurementioning
confidence: 99%
“… 7 Accumulating evidence also has demonstrated that the circulating levels of VEGF are elevated in various cancers, including colorectal cancer, 8 lung cancer, 9 gastric cancer, 10 endometrial cancer, 11 breast cancer, 12 OC. 13 Thus, VEGF is a focus of interest with respect to vascular research and oncology.…”
Section: Introductionmentioning
confidence: 99%